2010
DOI: 10.1245/s10434-010-1100-6
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy-Assisted Distal Gastrectomy with Jejunal Pouch Interposition

Abstract: The incidence of early gastric cancer (EGC) has been increasing in Asian countries as a result of the development of diagnostic modalities such as endoscopic examination and barium meal examination. Currently in Japan, patients with EGC account for more than half of all patients with gastric cancer. More than 90% of patients with EGC can be cured only by curative gastrectomy. Therefore, in the treatment of EGC, not only complete removal of cancer cells but also minimal invasiveness and improvement of patient q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In addition to total and proximal gastrectomy, the JP reconstruction after distal gastrectomy is designed to increase the food volume, allow the food to pass more gradually through the duodenum and first part of the jejunum, and prevent regurgitate esophagitis and residual gastritis. 6,12,23,30 To this end, Lee et al 23 reported that JP after distal gastrectomy for EGC resulted in a low incidence of bile reflux gastritis, appetite change, heartburn, reductions in physical strength and daily activity levels, and greater food intake with each meal compared with the preoperative metric and reduced body weight loss observed with Billroth-II gastrojejunostomy. Thus, JP after distal gastrectomy is a feasible procedure that may produce a satisfactory outcome in terms of alleviating postgastrectomy syndrome; however, it requires a longer operation time.…”
Section: Jp After Proximal or Distal Gastrectomymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to total and proximal gastrectomy, the JP reconstruction after distal gastrectomy is designed to increase the food volume, allow the food to pass more gradually through the duodenum and first part of the jejunum, and prevent regurgitate esophagitis and residual gastritis. 6,12,23,30 To this end, Lee et al 23 reported that JP after distal gastrectomy for EGC resulted in a low incidence of bile reflux gastritis, appetite change, heartburn, reductions in physical strength and daily activity levels, and greater food intake with each meal compared with the preoperative metric and reduced body weight loss observed with Billroth-II gastrojejunostomy. Thus, JP after distal gastrectomy is a feasible procedure that may produce a satisfactory outcome in terms of alleviating postgastrectomy syndrome; however, it requires a longer operation time.…”
Section: Jp After Proximal or Distal Gastrectomymentioning
confidence: 99%
“…Several modified gastrectomy techniques have been developed with the aim of preventing postgastrectomy issues, including reflux esophagitis, dumping syndrome, and loss of appetite. 6 The Roux-en-Y (RY) reconstruction is currently the most commonly performed procedure after total gastrectomy, because it is simple to perform and decreases esophageal reflux; however, RY reconstruction also has several adverse outcomes including postoperative dumping syndrome, impaired food intake, and a poor reservoir function. Thus, no optimal reconstruction method has yet become universally accepted.…”
mentioning
confidence: 99%
“…With the development of diagnostic techniques, such as endoscopy [1, 2], and the more widespread use of routine physical examinations [3, 4], patients with early gastric cancer now represent more than half the gastric cancer patients in Japan [5], with a 5‐year survival rate of 99.3 % for pT1a and 96.7 % for pT1b [6]. Due to these increases in survival rates, not only is there greater demand for treatment to cure gastric cancer, but also for decrease in operative invasiveness and loss of postoperative quality of life (QOL).…”
Section: Introductionmentioning
confidence: 99%